Antigen-driven selection of antibodies against SSA, SSB and the centromere 'complex', including a novel antigen, MIS12 complex, in human salivary glands. Issue 1 (14th October 2019) - Takeshita, Masaru; Suzuki, Katsuya; Kaneda, Yukari; Yamane, Humitsugu; Ikeura, Kazuhiro; Sato, Hidekazu; Kato, Shin; Tsunoda, Kazuyuki; Arase, Hisashi; Takeuchi, Tsutomu
Abstract : Objectives: Recent evidences have revealed that anti-SSA/SSB antibodies, the major autoantibodies in Sjögren's syndrome (SS), are produced in salivary glands. This study aims to clarify overall of autoantibody production at lesion site, including anti-centromere antibody (ACA)-positive SS. Methods: Antibodies of antibody-secreting cells in human salivary glands were produced as recombinant antibodies. The reactivity of these antibodies and their revertants were investigated by ELISA and newly developed antigen-binding beads assay, which can detect conformational epitopes. The target of uncharacterised antibodies was identified by immunoprecipitation and mass spectrometry. Autoantibody-secreting cells in salivary gland tissue were identified by immunohistochemistry using green fluorescent protein-autoantigen fusion proteins. Results: A total of 256 lesion antibodies were generated, and 69 autoantibodies including 24 ACAs were identified among them. Beads assay could detect more autoantibodies than ELISA, suggesting autoantibodies target to antigens with native conformation. After somatic hypermutations were reverted, autoantibodies drastically decreased antigen reactivity. We showed that MIS12 complex, a novel target of ACA, and CENP-C are major targets of ACA produced in salivary glands by examining cloned antibodies and immunohistochemistry, whereas few anti-CENP-B antibodies were detected. The target profiling of serum ACA from 269 patients with SS, systemic sclerosis (SSc), primary biliary cirrhosis (PBC) and healthy controls revealed that ACA-positive patients have antibodies against various sites of centromere complex regardless of disease. Conclusion: We showed direct evidences of antigen-driven maturation of anti-SSA/SSB antibody and ACA in SS lesion. ACA recognises centromere 'complex' rather than individual protein, and this feature is common among patients with SS, SSc and PBC.